Kinetics of Anaerobic Digestion of Dairy Fat Waste with Saponification Pre-Treatment - Rifki Wahyu Kurnianto; Wiratni Budhijanto; Rochim Bakti Cahyono (Departemen Teknik Kimia Fakultas Teknik Universitas Gadjah Mada, 2019)
Anaerobic digestion has been an attractive field of research in the era of energy crisis. Biogas, which is the product of anaerobic digestion, provides alternative energy, while at the same time it also prevents pollution due to organic waste accumulation. Among various organic wastes, dairy fat waste is a potential substrate for anaerobic digestion. Fat waste has high theoretical biogas potential because of its high lipid content. However, anaerobic digestion of organic waste with high lipid content is quite challenging. The main obstacle in anaerobic digestion of fat waste is its tendency to form insoluble floating layer on top of the liquid phase. This phenomenon hinders the access of hydrolytic bacteria to the substrate. Saponification is one of the methods to increase the solubility of the floating layer and hence to improve the availability of substrate for the bacteria. Saponification changes the lipid content into soap which has both polar and non-polar functional groups and the polar side will increase the solubility of the substrate in water. This study evaluated the effect of different dosage of base added as the reactant during saponification pre-treatment on the productivity of anaerobic digestion of dairy fat waste. The kinetics of the anaerobic digestion process was analyzed by mean of mathematical model. The variations of the alkaline dosages studied for saponification pre-treatment were 0.04 mol base/g sCOD; 0.02 mol base/g sCOD; and no pre-treatment for control reactor. This study proved that saponification increased the solubility of dairy fat waste. This result was confirmed by the hydrolysis constant value (kH) of 0.00782/day for reactor with saponification, which was twenty times of magnitude higher than the kH value of 0.00032/day in the reactor without saponification. However, the exposure to high pH during the saponification pre-treatment might somewhat inhibit indigenous acidogenic bacteria in the waste which results in lower methane yield in the reactors with saponification to be compared to the control reactor. A B S T R A KPeruraian anaerobik merupakan salah satu bidang riset yang sangat menarik perhatian dalam era krisis energi. Biogas tidak hanya menyediakan energi alternatif, tetapi juga dapat mencegah pencemaran akibat limbah organik. Limbah lemak susu adalah substrat yang potensial untuk proses peruraian anaerobik karena memiliki potensi biogas teoritis yang tinggi akibat kandungan lemaknya yang tinggi. Namun, peruraian anaerobik dari limbah organik dengan kandungan lemak yang tinggi memiliki tantangan tersendiri. Hambatan utama dalam peruraian anaerobik dari limbah lemak susu adalah kecenderungan untuk membentuk lapisan padatan yang tidak larut dan mengapung di bagian atas fase cair. Fenomena ini menghambat akses bakteri hidrolisis terhadap substrat. Saponifikasi adalah salah satu cara untuk meningkatkan kelarutan lapisan padatan tersebut, sehingga meningkatkan ketersediaan substrat untuk bakteri. Saponifikasi akan mengubah kandungan lemak menjadi sabun yang memiliki gugus fungsi polar maupun non-polar. Gugus fungsi yang bersifat polar akan meningkatkan kelarutan substrat dalam air. Studi ini mengevaluasi pengaruh dari berbagai dosis larutan basa yang ditambahkan sebagai reaktan selama perlakuan awal saponifikasi terhadap peruraian anaerobik limbah lemak susu. Kinetika proses peruraian anaerobik dianalisis dengan menggunakan model matematika. Variasi dosis yang diamati pengaruhnya untuk perlakuan awal saponifikasi adalah 0,04 mol basa/g sCOD; 0,02 mol basa/g sCOD; dan nol (tanpa perlakuan awal saponifikasi). Dari penelitian ini, terbukti bahwa saponifikasi berhasil meningkatkan kelarutan limbah lemak susu dan juga ditunjukkan oleh nilai konstanta hidrolisis (kH) 0,00782/hari lebih tinggi dua puluh kali lipat dibandingkan dengan nilai kH 0,00032/hari pada reaktor tanpa saponifikasi. Akan tetapi, penelitian ini juga mengindikasikan bahwa bakteri asidogenik bawaan substrat terhambat kinerjanya oleh paparan pH yang tinggi selama perlakuan awal saponifikasi berlangsung sehingga hasil gas metan yang diperoleh lebih rendah daripada reaktor kontrol.